Fast growth rate of a right atrial myxoma - Gewehr,Douglas Mesadri (2022)
ABSTRACT Primary cardiac tumors are rare, with an incidence between 0.0017 and 0.19%, and are asymptomatic in up to 72% of cases. Approximately 75% of tumors are benign, and nearly 50% of these are myxomas. Concerning location, 75% of myxomas are in the left atrium, 15 to 20% in the right atrium, and more rarely in the ventricles. The finding of cardiac myxomas usually implies immediate surgical excision to prevent embolic events and sudden cardiac death. Reports with documented growth rate are rare, and the actual growth rate remains a controversial issue. We report the rapid growth rate of a right atrial myxoma in an oligosymptomatic 69-year-old patient, with negative previous echocardiographic history in the last two years, who refused surgery upon diagnosis, enabling monitoring of myxoma growth.